2018
DOI: 10.1177/2047487318807977
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oxygen-uptake efficiency slope in healthy children and children with heart disease: Generation of appropriate reference values for the OUES variable

Abstract: Background: Oxygen-uptake efficiency slope (OUES) is an objective measure of functional capacity that does not require a maximal effort but is considerably dependent on anthropometric variables and requires the generation of an appropriate reference value in children. This study aimed to establish normal reference values for OUES/kg in children with and without congenital heart diseases. Besides that, reference values are presented secondarily for OUES per body surface area (OUES/BSA). Design: Cross-sectional.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Some important predictive outcomes from the CPET, as OEUS, were not given in most studies. 38 The dropout rate was 15%, most studies did not describe the exact reasons for patients who discontinued participating in the training programme, possibly these patients experienced negative effects of the training. Another important question that remains unanswered is what the effect of training is on the long-term.…”
Section: Limitations Of Included Studiesmentioning
confidence: 99%
“…Some important predictive outcomes from the CPET, as OEUS, were not given in most studies. 38 The dropout rate was 15%, most studies did not describe the exact reasons for patients who discontinued participating in the training programme, possibly these patients experienced negative effects of the training. Another important question that remains unanswered is what the effect of training is on the long-term.…”
Section: Limitations Of Included Studiesmentioning
confidence: 99%
“…No results in adults were found. Five studies reported oxygen uptake efficiency slope (OUES) values, two in adults [42,43], two in a pediatric population [29,34], and one study reporting up to young adulthood (21 years of age) [44].…”
Section: Breathing Frequency At Peak Exercisementioning
confidence: 99%
“…1 When there are significant differences in these parameters between patients and healthy controls, as in the study by Hossri et al., care has to be taken when interpreting the results. 4 A low exercise capacity might be caused just by an increased body mass, for example.…”
Section: Oxygen Uptake Efficiency Slopementioning
confidence: 99%